In The Wake: Black Girl Lessons on Collective Care. (14th October 2022) - Reynolds, Aja
Abstract : This article centers Black girl leadership as a survival guide in this unprecedented moment of combating two pandemics, Covid-19 and extrajudicial killings of Black people. I recall lessons learned during my ethnographic research with Black girls in Chicago in which loss and grieving was often and premature. This piece is a response to Christina Sharpe's "wake work" conceptualization that challenges the collective care Black people specifically must engage both with our living and dead.